Klas Torstensson in Conversation - Goldman, Jonathan (Circuit, 2004)
During his stay as guest composer at the MNM festival, Klas Torstensson speaks about his musical approach with Jonathan Goldman. After hearing his monumental Licks and Brains tryptich, Torstensson discusses his views on Netherland-style Minimalism, the interactive relationship that he aims at between composer and performer, his concept of networks and fragmentation as compositional techniques, and the primordial role of intuition in musical development.